Cutting blade, glass fiber cutting device, glass fiber manufacturing method, and cutting blade manufacturing method

The cutting blade with a cemented carbide edge, carbon tool steel base, and minimized voids in the joint, joined using a fiber laser, addresses crack issues in glass fiber cutting, ensuring stable production of chopped strands.

JP7765275B2Active Publication Date: 2025-11-06NIPPON ELECTRIC GLASS CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2021206954
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-12-21
Publication Date
2025-11-06
Estimated Expiration
2041-12-21

AI Technical Summary

Technical Problem

Existing glass fiber cutting blades experience cracks at the joint due to excessive heat application from certain types of lasers, leading to potential breakage during extended use.

Method used

A cutting blade design featuring a cemented carbide cutting portion, a carbon tool steel base portion, and a joint containing nickel or cobalt with a dendrite layer, where voids are minimized to enhance bonding strength and prevent cracks, using a fiber laser for joining to form the dendrite layer.

Benefits of technology

The design effectively prevents cracks at the joint, ensuring stable production of chopped glass fibers by maintaining strong bonding between the cutting edge and base, thus extending the blade's lifespan.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007765275000002
    Figure 0007765275000002
  • Figure 0007765275000003
    Figure 0007765275000003
  • Figure 0007765275000004
    Figure 0007765275000004
Patent Text Reader

Abstract

To reliably suppress generation of a crack in a junction of a cutting blade.SOLUTION: A cutting blade 4 includes: a blade part 6 including a cemented carbide; a substrate part 7 including a carbon tool steel; and a junction 8 including nickel or cobalt and joining the blade part 6 to the substrate part 7. The junction 8 includes a dendrite layer 9. The number of voids V having 50 μm or more of equivalent circle diameter is two or less per 1 mm2 at any orthogonal cross section of the junction 8 relative to a longitudinal direction X of the cutting blade 4.SELECTED DRAWING: Figure 4
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a technique for cutting glass fibers to a predetermined length. [Background technology]

[0002] The glass fiber cutting device is equipped with a cutting roll equipped with multiple cutting blades and a rubber contact roll facing it. By continuously supplying long glass fibers between the cutting roll and the contact roll, chopped glass fibers (chopped strands) are produced. The chopped glass fibers are used as reinforcing materials in a wide range of fields, including automobiles, electrical and electronic devices, and housing equipment.

[0003] For example, Patent Document 1 discloses a cutting blade having a cutting portion made of cemented carbide, a base portion made of carbon tool steel, and a joint (alloy layer) joining the cutting portion and the base portion. The joint is made of a nickel alloy or a cobalt alloy.

[0004] This cutting blade has excellent wear resistance because the cutting portion is made of cemented carbide, and excellent impact resistance because the base portion is made of carbon tool steel. Furthermore, because nickel or cobalt is melted into the carbon tool steel and cemented carbide and integrated, the bonding strength between the cutting portion and the base portion is also high. This has the advantage that the cutting blade can be used for a long period of time and is less likely to break even if an excessive impact load is applied to the cutting blade. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Laid-Open No. 2008-100348 Summary of the Invention [Problem to be solved by the invention]

[0006] This type of cutting blade is manufactured by placing a bonding material made of nickel or cobalt between the blade portion and the base portion, and then heating the bonding material with laser irradiation to bond the blade portion and the base portion.

[0007] However, depending on the type of laser used (e.g., CO2 laser), excessive heat may be applied to the joint between the blade and the base, resulting in the problem of cracks occurring at the joint when such cutting blades are used for extended periods of time. Such cracks may cause the cutting blade to break.

[0008] An object of the present invention is to reliably prevent cracks from occurring at the joint of the cutting blade. [Means for solving the problem]

[0009] (1) The present invention, which has been invented to solve the above problems, is a cutting blade comprising a cutting portion containing cemented carbide, a base portion containing carbon tool steel, and a joint portion which joins the cutting portion and the base portion and contains nickel or cobalt, wherein the joint portion has a dendrite layer, and in any cross section perpendicular to the longitudinal direction of the cutting blade, voids with a circle equivalent diameter of 50 μm or more are present within 1 mm 2 The characteristic of this method is that there are two or less voids per unit area. Here, the "orthogonal cross section of the joint" includes the interface between the joint and the blade portion and the interface between the joint and the base portion. The "circle equivalent diameter" means the diameter of a circle having an area equal to the area of ​​the void. The "arbitrary orthogonal cross section" means a randomly selected orthogonal cross section in the longitudinal direction of the cutting blade.

[0010] This improves the bond strength between the cutting edge and the base due to the anchoring effect of the dendrite layer. It also reduces the number of large voids (cavity defects) in the bonded area, effectively preventing cracks from forming at the bonded area.

[0011] (2) In the above configuration (1), it is preferable that the dendrite layer is formed over the entire area in the thickness direction of the cutting blade.

[0012] This further improves the bonding strength between the blade portion and the base portion.

[0013] (3) In the above configuration (1) or (2), it is preferable that the number of voids contained in the dendrite layer in an orthogonal cross section of the joint is 10 or less.

[0014] In this way, the bonding strength due to the dendrite layer can be more reliably improved.

[0015] (4) In any of the above (1) to (3), in the orthogonal cross section of the joint, voids of 20 μm or more in circle equivalent diameter are not more than 1 mm 2 It is preferable that there are four or less per unit.

[0016] This reduces the number of small voids contained in the joint, making it more difficult for cracks to occur that originate from voids.

[0017] (5) In any of the above (1) to (4), the number of voids with a circle equivalent diameter of 10 μm or more at the interface between the joining portion and the cutting edge in the orthogonal cross section of the joining portion is 0.1 mm 2 Preferably, there are three or less per unit.

[0018] Generally, cracks are particularly likely to occur at the interface between the joint and the blade portion, but with the above-described configuration, the number of very small voids at the interface between the joint and the blade portion is reduced, making cracks less likely to occur at the interface between the joint and the blade portion.

[0019] (6) In any of the configurations (1) to (5) above, the number of voids with a circle-equivalent diameter of 50 μm or more contained in an orthogonal cross section of the joint at one longitudinal end of the cutting blade may be greater than the number of voids with a circle-equivalent diameter of 50 μm or more contained in an orthogonal cross section of the joint at the other longitudinal end of the cutting blade, and the thickness of the dendrite layer contained in the joint at one longitudinal end of the cutting blade may be greater than the thickness of the dendrite layer contained in the joint at the other longitudinal end of the cutting blade.

[0020] For example, as in the configuration (10) described below, if the scanning speed of the fiber laser at one end of the joining material is slower than the scanning speed of the fiber laser at the other end of the joining material during the joining process, the amount of heat supplied to the one end of the joining material will be relatively large. As a result, in the manufactured cutting blade, the number of voids with a circle-equivalent diameter of 50 μm or more in the orthogonal cross section of one end of the joining material may be greater than the number of voids with a circle-equivalent diameter of 50 μm or more in the orthogonal cross section of the other end of the joining material. In this case, there is a concern that cracks originating from voids may be more likely to occur at one end of the joining material than at the other end of the joining material. However, with the above configuration, the thickness of the dendrite layer at one end of the joining material is greater than the thickness of the dendrite layer at the other end of the joining material, resulting in a relatively high joining strength at one end of the joining material. Therefore, the joining material remains less susceptible to cracks.

[0021] (7) The present invention, which was invented to solve the above problems, is a glass fiber cutting device, characterized in that it is equipped with a cutting blade having any of the configurations (1) to (6) above, and cuts the glass fiber to a predetermined length using the cutting blade.

[0022] In this way, chopped strands can be produced stably.

[0023] (8) The present invention, which was invented to solve the above problems, is a method for manufacturing glass fibers, characterized by comprising a cutting step of cutting glass fibers to a predetermined length using a cutting blade having any one of the configurations (1) to (6) above.

[0024] In this way, chopped strands can be produced stably.

[0025] (9) The present invention, which was invented to solve the above-mentioned problems, is characterized by comprising a joining preparation step in which a joining material containing nickel or cobalt is placed between a cutting portion containing cemented carbide and a base portion containing carbon tool steel, and a joining step in which, after the joining preparation step, the joining material is heated by irradiating it with a fiber laser to join the cutting portion and the base portion.

[0026] By using a fiber laser in this joining process, a dendrite layer is formed at the joint of the manufactured cutting blade, and the number of voids is significantly reduced, making it possible to provide a cutting blade that is less susceptible to cracks originating from voids at the joint.

[0027] (10) In the configuration of (9) above, in the joining process, it is preferable that the fiber laser is scanned from one end side to the other end side of the joining material along the longitudinal direction of the cutting blade, and that the scanning speed of the fiber laser at one end of the joining material is slower than the scanning speed of the fiber laser at other parts including the other end of the joining material.

[0028] By relatively slowing the scanning speed of the fiber laser at one end of the joining material in this way, the amount of heat supplied from the fiber laser to the one end of the joining material becomes relatively large. This amount of heat melts the one end of the joining material while simultaneously preheating the other portion of the joining material, including the other end. Therefore, even if the scanning speed of the fiber laser at the other portion of the joining material, including the other end, is relatively fast, the joining material can be sufficiently melted. Therefore, the blade portion and the base portion can be firmly joined while shortening the time required for the joining process. [Effects of the Invention]

[0029] According to the present invention, it is possible to reliably prevent cracks from occurring at the joint portion of the cutting blade. [Brief explanation of the drawings]

[0030] [Figure 1] 1 is a side view showing a glass fiber cutting device according to an embodiment of the present invention. [Figure 2] FIG. 2 is a front view of a cutting blade according to an embodiment of the present invention. [Figure 3] 3 is a cross-sectional view taken along the line AA in FIG. 2. [Figure 4] 1 is an example of an electron microscope image of a cross section of a joint taken along a plane perpendicular to the longitudinal direction of a cutting blade. [Figure 5] 1 is an example of an electron microscope image of a cross section of a joint taken along a plane perpendicular to the longitudinal direction of a cutting blade. [Figure 6] FIG. 4 is a diagram schematically illustrating a cross section of a joint portion along the longitudinal direction of a cutting blade. [Figure 7] FIG. 3 is a flowchart showing a method for manufacturing a cutting blade according to an embodiment of the present invention. [Figure 8] 10 is a cross-sectional view showing a joining preparation step included in the manufacturing method of the cutting blade. FIG. [Figure 9] 4 is a cross-sectional view showing a joining step included in the manufacturing method of the cutting blade. FIG. [Figure 10] FIG. 10 is a front view showing a joining step included in the manufacturing method of the cutting blade. DETAILED DESCRIPTION OF THE INVENTION

[0031] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS Hereinafter, embodiments of the present invention will be described with reference to the drawings, in which X, Y, and Z represent an orthogonal coordinate system.

[0032] As shown in FIG. 1, a glass fiber cutting device 1 according to this embodiment includes a cutting roll 2 and a contact roll 3 opposed to the cutting roll 2.

[0033] The cutting roll 2 has a plurality of cutting blades 4 arranged radially on its outer circumferential surface. In this embodiment, the plurality of cutting blades 4 are provided on the outer circumferential surface of the cutting roll 2 at equal intervals in the circumferential direction.

[0034] The contact roll 3 has a rubber layer 5 on its outer circumferential surface.

[0035] In the cutting step included in the glass fiber manufacturing method according to this embodiment, long glass fibers G are continuously supplied between a cutting roll 2 and a contact roll 3 while these rolls 2 and 3 are rotated, and glass fibers (chopped strands) S are produced that are cut to a predetermined length (for example, 1.5 to 12 mm) by a cutting blade 4. The cut glass fibers S are used, for example, in fiber reinforced thermoplastics (FRTP) and glass fiber reinforced cement (GRC). Note that the glass fibers G and S may be monofilaments, but in this embodiment, they are made by bundling a large number of monofilaments using a sizing agent.

[0036] As shown in FIGS. 2 and 3, the cutting blade 4 includes a blade portion 6, a base portion 7, and a joint portion 8 that joins a base end 6b of the blade portion 6 and a tip end 7a of the base portion 7.

[0037] The thickness (dimension in the Z direction) of the cutting blade 4 is preferably 0.3 to 4.5 mm, and more preferably 0.3 to 1.5 mm. If the thickness of the cutting blade 4 is too small, the strength of the cutting blade 4 decreases, and if the thickness of the cutting blade 4 is too large, it becomes difficult to shorten the cutting length of the glass fibers G.

[0038] The cutting edge 6 is made of cemented carbide, and the tip 6a is a sharp cutting edge. As the cemented carbide, an extremely hard alloy made by blending and sintering powder of a metal element carbide and powder of a metal can be used. The cemented carbide has excellent wear resistance, and even if worn, it is preferable that it can be reused by polishing. Specifically, WC-Co, WC-TaC-Co, WC-TiC-Co, and WC-TiC-TaC-Co alloys can be used, and the thermal expansion coefficient of these alloys is 48 to 62 × 10 in the temperature range of 25 to 200 °C. -7 / ℃.

[0039] The cutting portion 6 can be obtained by blending and sintering 85 to 95 mass % tungsten carbide (WC) powder with an average particle size of 0.3 to 1.0 μm and 5 to 15 mass % cobalt (Co) powder to form it into a predetermined shape and size (for example, the dimension from the base end 6b to the tip 6a of the cutting portion 6 is 3 to 7 mm).

[0040] The base portion 7 is made of carbon tool steel. Carbon tool steel is obtained by quenching and tempering iron containing carbon. It is preferable that the carbon tool steel has excellent impact resistance. Specifically, SK-5, SK-2, etc. can be used, and the thermal expansion coefficient of these is 100 to 120 × 10 in the temperature range of 25 to 200°C. -7 / ℃.

[0041] The base portion 7 can be obtained by quenching and tempering iron (Fe) containing, for example, 0.8 to 1.3 mass % carbon (C) to form it into a predetermined shape and size (for example, the dimension from the base end 7b to the tip end 7a of the base portion 7 is 12 to 20 mm).

[0042] The Vickers hardness of the blade portion 6 is preferably 2.0 to 3.0 times that of the base portion 7. If the ratio of the Vickers hardness of the blade portion 6 to that of the base portion 7 becomes too small, the entire cutting blade 4 becomes prone to excessive deformation (stickiness) when cutting the glass fibers G, and particularly when the contact roll 3 becomes worn, the blade portion 6 does not accurately contact the glass fibers G, making cutting defects more likely to occur. Also, if the ratio of the Vickers hardness of the blade portion 6 to that of the base portion 7 becomes too large, the difference in thermal expansion coefficient between the base portion 7 and the blade portion 6 becomes large, which may make it difficult to stably join them.

[0043] The joint 8 is formed from a nickel alloy layer or a cobalt alloy layer. In particular, the nickel alloy layer has a thermal expansion coefficient (40 to 47×10 in the temperature range of 30 to 300°C) that is close to that of cemented carbide. -7 / °C), residual stress is less likely to occur in the joint 8, and deformation of the joint 8 can be suppressed.

[0044] As shown in FIG. 4, in an orthogonal cross section of the joint 8 relative to the longitudinal direction X of the cutting blade 4 (hereinafter simply referred to as "the orthogonal cross section of the joint 8"), the joint 8 has a dendrite layer 9. The orthogonal cross section of the joint 8 is a cross section along the Y direction, such as the AA cross section in FIG. 2. The dendrite layer 9 is a layer containing dendrites (branched crystals) D. The dendrites D are, for example, Ni-Co precipitates, and are presumed to have precipitated as a result of a component of the cutting edge 6 (for example, Co) diffusing into the joint 8 (for example, Ni).

[0045] In this embodiment, the dendrite layer 9 is formed in a region of the joint 8, including the vicinity of the interface 8a with the blade portion 6. The dendrite layer 9 is preferably formed uniformly throughout the entire thickness direction Z of the cutting blade 4. The dendrites D contained in the dendrite layer 9 spread in a dendritic form from the interface 8a with the blade portion 6 into the joint 8, thereby improving the adhesion between the joint 8 and the blade portion 6 due to the anchor effect. The dendrite layer 9 may be formed in a region of the joint 8, including the vicinity of the interface 8b with the base portion 7. In this case, the adhesion between the joint 8 and the base portion 7 is improved due to the anchor effect. Therefore, from the viewpoint of improving the bonding strength of the joint 8, the dendrite layer 9 is preferably formed in the region of the joint 8, from the interface 8a with the blade portion 6 to the interface 8b with the base portion 7 (the entire joint 8 in the Y direction). Note that the thickness of the dendrite layer 9 does not need to be constant in the longitudinal direction X of the cutting blade 4. For example, as will be described later, the thickness T1 of the dendritic layer 9 included in one end 8c of the joint 8 in the longitudinal direction X may be different from the thickness T2 of the dendritic layer 9 included in the other end 8d of the joint 8 in the longitudinal direction X (see Figure 6).

[0046] Although not shown, a diffusion layer is formed on the base end 6b side of the blade portion 6, where the components of the joint portion 8 (for example, Ni) are diffused into the blade portion 6.

[0047] As shown in FIG. 5, in an orthogonal cross section of the joint 8, the joint 8 may contain voids V (shown in black in FIG. 5). However, in any orthogonal cross section of the joint 8, voids V of 50 μm or more in circle equivalent diameter are not allowed to exceed 1 mm. 2 Voids V with a circular equivalent diameter of 50 μm or more are not more than 2 per 1 mm 2 It is preferable that there is one or less voids per void, and more preferably zero voids per void, so that cracks originating from the voids V can be reliably prevented from occurring in the joint 8. Note that the arbitrary orthogonal cross section may be selected at random from one location in the center of the longitudinal direction X, or one location each from the center of the longitudinal direction X, one end 8c, and the other end 8d.

[0048] In any orthogonal cross section of the joint 8, the dendritic layer 9 preferably contains 10 or less voids V.

[0049] In any orthogonal cross section of the joint 8, voids V of 20 μm or more in circle equivalent diameter are 2 Preferably, there are four or fewer per unit, more preferably two or fewer per unit, and even more preferably zero per unit.

[0050] At the interface 8a with the cutting edge 6 in any orthogonal cross section of the joint 8, the void V of 10 μm or more in circle equivalent diameter is 0.1 mm 2 The number of voids V having a circle equivalent diameter of 10 μm or more is preferably 3 or less, more preferably 2 or less, and even more preferably 0, per 0.1 mm2 including the interface portion 8a. 2 is the number of voids V contained in each region.

[0051] The number of voids V with a circle-equivalent diameter of 50 μm or more contained in an orthogonal cross section of one end 8c of the joint 8 in the longitudinal direction X may be greater than the number of voids V with a circle-equivalent diameter of 50 μm or more contained in an orthogonal cross section of the other end 8d of the joint 8 in the longitudinal direction X. In this case, as shown in FIG. 6, it is preferable that the thickness (dimension in the Y direction) T1 of the dendrite layer 9 contained in the one end 8c of the joint 8 in the longitudinal direction X is greater than the thickness T2 of the dendrite layer 9 contained in the other end 8d of the joint 8 in the longitudinal direction X. As a result, even if the number of voids V is relatively large at one end 8c of the joint 8, the thickness of the dendrite layer 9 is increased at that portion 8c, thereby maintaining a state in which cracks are less likely to occur in the joint 8. Note that FIG. 6 is a cross section of the joint 8 taken along the longitudinal direction X, and schematically shows the area in which the dendrite layer 9 is formed (the cross-hatched area). The thicknesses T1 and T2 of the dendritic layer 9 may be measured, for example, in an orthogonal cross section of the joint 8 where the number of voids V is measured. When the thickness of the dendritic layer 9 varies within the orthogonal cross section of the joint 8, the thicknesses T1 and T2 are defined, for example, by the maximum thickness of the dendritic layer 9 included in the cross section.

[0052] In addition, when the thickness of the dendrite layer 9 varies in the longitudinal direction X, although not shown in the figure, the thickness of the diffusion layer (a layer in which components of the joint 8 have diffused into the blade portion 6) included in one end portion of the blade portion 6 in the longitudinal direction X (the end portion on the side of one end 8c of the joint 8) may also be larger than the thickness of the diffusion layer included in the other end portion of the blade portion 6 in the longitudinal direction X (the end portion on the side of the other end 8d of the joint).

[0053] Next, a method for manufacturing the cutting blade 4 configured as above will be described.

[0054] As shown in FIG. 7, this manufacturing method includes a blade portion preparation step S1 for preparing a blade portion 6, a base portion preparation step S2 for preparing a base portion 7, a joining preparation step S3 for arranging a joining material 11 between the blade portion 6 and the base portion 7, a joining step S4 for joining the blade portion 6 and the base portion 7 using the joining material 11, and a blade sharpening step S5 for grinding the tip 6a of the blade portion 6 joined to the base portion 7.

[0055] In the blade portion preparation step S1, a cemented carbide alloy having a predetermined size and shape (for example, a dimension from the base end 6b to the tip 6a of the blade portion 6 of 3 to 7 mm) is prepared as the blade portion 6 by blending and sintering 85 to 95 mass% of tungsten carbide (WC) powder with an average particle size of 0.3 to 1.0 μm and 5 to 15 mass% of cobalt (Co) powder.

[0056] In the base preparation step S2, the base 7 is prepared from carbon tool steel formed into a predetermined shape and size (for example, the dimension from the base end 7b to the tip end 7a of the base 7 is 12 to 20 mm) by quenching and tempering iron (Fe) containing 0.8 to 1.3 mass % carbon (C).

[0057] 8, in the joining preparation step S3, the base portion 7, the blade portion 6, and the joining material 11 are arranged so that the joining material 11 is sandwiched from both sides by the tip end 7a of the base portion 7 and the base end 6b of the blade portion 6, which are aligned with each other in the longitudinal direction X. The joining material 11 is, for example, a nickel foil or a cobalt foil having a thickness of 0.2 to 0.5 mm.

[0058] As shown in FIG. 9, in the joining step S4, the joining material 11 is heated by irradiating it with a fiber laser L. This locally heats the joining material 11 and its vicinity, forming a joining portion 8 that joins the blade portion 6 and the base portion 7. The joining portion 8 is formed of a nickel alloy layer or a cobalt alloy layer. The alloy layer is formed when nickel or cobalt forms a solid solution with iron, which is the main component of carbon tool steel, and melts into the cemented carbide alloy. The fiber laser L is a type of solid-state laser that uses an optical fiber as an amplification medium.

[0059] By using the fiber laser L in the joining step S4 in this way, as described above, a dendrite layer 9 is formed at the joint 8, and the number of voids V at the joint 8 is also significantly reduced. Therefore, cracks originating from the voids V are less likely to occur at the joint 8.

[0060] The wavelength of the fiber laser L is, for example, 1.06 μm. The laser output of the fiber laser L is preferably 500 to 1000 W, and more preferably 600 to 800 W. The spot diameter of the fiber laser L is preferably 50 to 300 μm, and more preferably 100 to 200 μm.

[0061] 10, the fiber laser L is scanned from one end 11c side to the other end 11d side of the bonding material 11 along the longitudinal direction X. The scanning speed of the fiber laser L may be constant or may vary in the longitudinal direction X of the bonding material 11.

[0062] When changing the scanning speed of the fiber laser L, it is preferable to set the scanning speed R1 of the fiber laser L at one end 11c (the end on the welding start side) of the joining material 11 slower than the scanning speed R2 of the fiber laser L at other portions including the other end 11d (the end on the welding end side) of the joining material 11. The scanning speed R2 is, for example, 1.2 to 2.0 times the scanning speed R1. In this way, the amount of heat supplied from the fiber laser L to the one end 11c of the joining material 11 becomes relatively large. Therefore, the amount of heat supplied to the one end 11c of the joining material 11 can melt the one end 11c of the joining material 11 and simultaneously preheat the other portions including the other end 11d of the joining material 11. Therefore, since the other portions including the other end 11d of the joining material 11 are already in a state where they are easily melted with a small amount of heat, there is an advantage that the joining material 11 can be sufficiently melted even if the scanning speed R2 of the fiber laser L is set relatively fast.

[0063] In this case, the number of voids V with a circle-equivalent diameter of 50 μm or more contained in an orthogonal cross section of one end 8c of the joint 8 is likely to be greater than the number of voids V with a circle-equivalent diameter of 50 μm or more contained in an orthogonal cross section of the other end 8d of the joint 8. On the other hand, the thickness T1 of the dendrite layer 9 contained in one end 8c of the joint 8 is likely to be greater than the thickness T2 of the dendrite layer 9 contained in the other end 8d of the joint 8. Therefore, the thickness of the dendrite layer 9 increases in the area where the number of voids V is greater, increasing the bonding strength, and maintaining a state in which cracks are less likely to occur in the joint 8.

[0064] In the sharpening process S5, the tip 6a of the cutting portion 6 is ground to form a sharp cutting edge. This produces a cutting blade 4 that includes the cutting portion 6, the base portion 7, and a joining portion 8 that joins the cutting portion 6 and the base portion 7. In the sharpening process S5, excess portions of the joining portion 8 that bulge outward from both main surfaces of the cutting blade 4 may be ground away, if necessary.

[0065] The present invention is not limited to the configuration of the above-described embodiment, nor is it limited to the above-described effects. The present invention can be modified in various ways without departing from the spirit of the present invention.

[0066] In the above embodiment, the method for producing glass fibers may include the following steps. The method for producing glass fibers may include a spinning step in which molten glass is drawn out from a number of nozzles formed at the bottom of the bushing and spun out as continuous thin glass filaments; a cooling step in which the glass filaments are cooled with a water spray; a bundling step in which a sizing agent is coated on the surface of a glass filter to bundle hundreds to thousands of glass strands into glass strands; a winding step in which the glass strands are wound up with a winder; and a cutting step in which the wound glass strands are cut to a predetermined length to form glass chopped strands. In the cutting step, the above-mentioned cutting device 1 (cutting blade 4) is used. [Example]

[0067] The present invention will be described in detail below based on examples, but the present invention is not limited to these examples.

[0068] (1)Blade part For the cutting edge, a cemented carbide alloy was prepared by blending tungsten carbide (WC) powder and cobalt (Co) powder, sintering the mixture, and molding it into a predetermined shape and size. (2) Base As the substrate, carbon tool steel formed into a predetermined size and shape by quenching and tempering iron (Fe) containing carbon (C) was prepared. (3) Bonding material (joint part) Nickel foil (thickness: 0.35 mm) was prepared as a bonding material.

[0069] In the comparative example, the cutting blade was manufactured by heating the bonding material with a CO2 laser to bond the cutting edge and the base. In contrast, in examples 1 and 2, the cutting blade was manufactured by heating the bonding material with a fiber laser to bond the cutting edge and the base. The orthogonal cross section of the bonded portion of each cutting blade was then observed with an electron microscope to check for the presence or absence of a dendrite layer and the number of voids in the orthogonal cross section of the bonded portion. The results are shown in Table 1.

[0070] [Table 1]

[0071] Table 1 above confirms that the cutting blade according to the comparative example, which was bonded using a CO laser, did not form a dendrite layer and had a large number of voids of various sizes in the orthogonal cross section of the bonded portion. In contrast, Table 1 above confirms that the cutting blades according to Examples 1 and 2, which were bonded using a fiber laser, formed a dendrite layer and had a very small number of voids of various sizes in the orthogonal cross section of the bonded portion. In particular, Example 2, in which the fiber laser output was set to 800 W, produced favorable results, with a densely formed dendrite layer and zero voids of various sizes. Furthermore, while the cutting blade according to the comparative example developed cracks originating from voids in the bonded portion after long-term use (e.g., 200 hours), the cutting blades according to Examples 1 and 2 did not develop cracks originating from voids in the bonded portion even after long-term use. [Explanation of symbols]

[0072] 1 cutting device 2 cutting rolls 3 Contact Roll 4 cutting blade 5 rubber layer 6 Blade 7 Base 8 Joint 9 Dendrite layer 11 Bonding material V Void (cavity defect) D Dendrite (branched crystal) G Glass fiber L Fiber Laser S chopped strands S1 Blade preparation process S2 Base preparation process S3 Bonding preparation process S4 Joining process S5 Blade sharpening process

Claims

1. A cutting blade comprising a blade portion including a cemented carbide alloy, a base portion including a carbon tool steel, and a joining portion that joins the blade portion and the base portion and that includes nickel or cobalt, the joint has a dendritic layer, In any cross section of the joint perpendicular to the longitudinal direction of the cutting blade, the number of voids having a circle equivalent diameter of 50 μm or more is 1 mm 2 There are two or less per item, the number of voids having a circle equivalent diameter of 50 μm or more included in the orthogonal cross section of the joint at one end of the longitudinal direction of the cutting blade is greater than the number of voids having a circle equivalent diameter of 50 μm or more included in the orthogonal cross section of the joint at the other end of the longitudinal direction of the cutting blade; A cutting blade characterized in that the thickness of the dendrite layer included in the joint at one end of the cutting blade in the longitudinal direction is greater than the thickness of the dendrite layer included in the joint at the other end of the cutting blade in the longitudinal direction.

2. The cutting blade according to claim 1 , wherein the dendrite layer is formed over the entire area of ​​the cutting blade in the thickness direction.

3. 3. The cutting blade according to claim 1, wherein the number of voids contained in the dendrite layer in the orthogonal cross section of the joint is 10 or less.

4. In the orthogonal cross section of the joint, voids with a circular equivalent diameter of 20 μm or more are found to be 1 mm 2 The cutting blade according to any one of claims 1 to 3, wherein the number of the grooves per groove is four or less.

5. At the interface between the joining portion and the cutting edge in the orthogonal cross section of the joining portion, voids having a circle equivalent diameter of 10 μm or more are present in a region of 0.1 mm 2 The cutting blade according to any one of claims 1 to 4, wherein the number of the cutting edges is three or less per blade.

6. A glass fiber cutting device comprising the cutting blade according to any one of claims 1 to 5, wherein the cutting blade cuts glass fibers to a predetermined length.

7. A method for producing glass fibers, comprising a cutting step of cutting glass fibers to a predetermined length with a cutting blade according to any one of claims 1 to 5.

8. a joining preparation step of disposing a joining material containing nickel or cobalt between a cutting portion containing cemented carbide and a base portion containing carbon tool steel; a joining step of heating the joining material by irradiating it with a fiber laser after the joining preparation step, and joining the blade portion and the base portion together, In the joining step, a fiber laser is scanned from one end side to the other end side of the joining material along the longitudinal direction of the cutting blade, and A method for manufacturing a cutting blade, characterized in that the scanning speed of a fiber laser at one end of the joining material is slower than the scanning speed of the fiber laser at other portions including the other end of the joining material.

Citation Information

Patent Citations

  • Manufacturing method of cutting blade for manufacturing glass chopped strand and cutting blade for manufacturing glass chopped strand

    JP2008100348A

  • Corrosion-resistant and wear-resistant built-up, method for forming corrosion-resistant and wear-resistant built-up and corrosion-resistant and wear-resistant valve

    JP2019117077A